Bubbles and incentives: A post-mortem of the Neuer Markt in Germany - Ulf von Kalckreuth; Leonid Silbermann (Deutsche Bundesbank, 2010)
This paper aims to shed light on some of the major allocative consequences of financial market bubbles. In March 1997, the Neuer Markt in Germany opened. Six years later, in June 2003, it closed forever. In the interim period lay the spectacular rise and fall of the first and most important European market for hi-tech stocks. Given investors' frenzy, the Neuer Markt was a special kind of natural experiment. For some time, financing constraints were virtually non-existent. Our model of corporate financing shows that bubbles on financial markets will induce entrepreneurs and providers of external finance to enter the 'wrong' contract. Incentive compatibility constraints designed to guarantee that corporate decision-makers behave constructively turn out to be invalid, and managers will know this before shareholders do. Thus, faulty valuation by stock markets may directly induce destructive corporate behaviour: slack, empire building, excessive risk-taking, and fraud. At the time of the IPO, a huge amount of liquidity is injected into the companies, and a dynamic analysis of the balance sheet ratios and income statement items in the following years can teach us the ways in which this liquidity is diffused. We analyse the corresponding dynamics of total assets, tangible assets and equity, as well as the evolution of sales and profits for 204 German non-financial companies out of a total of 326 companies that had their IPO at the Neuer Markt. On the basis of consecutive annual accounts, we retrace the events using a dynamic flow of funds analysis. We assess the explanatory power of our model using non-parametric methods [Median tests, Wilcoxon-Mann-Whitney tests, Kolmogorov-Smirnov tests] and quantile regressions. Our results indicate that valuation has strong and systematic effects on incentives. Experience, as proxied by age at IPO, is shown to have a beneficial effect, whereas support by VC and PE firms does not seem to matter for the success of the enterprises considered.
Keywords: G32; D82; D83; D92; C14; C21; 330; Bubbles; corporate governance; quantile regressions; nonparametric statistics; Neuer Markt; Wertpapieremission; Risikokapital; Corporate Governance; Bubbles; Börsenkrise; Unternehmensbewertung; Asymmetrische Information; Ökonomischer Anreiz; Deutschland